Vaccination against human papillomavirus among 865 female students from the health professions in central Greece: a questionnaire-based cross-sectional study - Papagiannis, Dimitrios (Dove Medical Press, 2013)
BACKGROUND: There are still sparse data on vaccination coverage against human papillomavirus (HPV) among students in the health professions. The aim of this study was to investigate HPV vaccination coverage in female students from the health professions in Greece. METHODS: A self-administered, anonymous questionnaire was distributed to second-year and third-year female students pursuing degrees in medicine, nursing, and paramedical health disciplines in central Greece. RESULTS: Overall vaccination coverage was 44.3%. The major reason for lack of vaccination was fear about safety of the vaccine. Participants who had received information about safety of the vaccine from the mass media and paramedical students had lower vaccination coverage in comparison with students who had received information about vaccine safety from alternative sources. CONCLUSION: Further quantitative and qualitative research is needed to design educational activities targeting female students in the health professions in order to create a positive domino effect and improve HPV vaccination coverage levels in Greece.